A stopping rule for facilities location algorithms - Love, Robert F.; Yeong, Yong Wee; McMaster University, Faculty of Business (My University, 1980)
The single facility location model with Euclidean distances and its multi-facility and ℓp distance generalizations are considered. With present algorithms a user is unable to decide how close to optimal any given feasible solution is. This article describes a procedure for calculating a lower bound on the optimal objective function when a proposed solution is given.
12, 4 leaves ; Includes bibliographical references (leaves 11-12). ; Cover title.;"September, 1980."
Keywords: Industrial location > Mathematical models Commercial geography > Mathematical models